Mitotic Errors Promote Genomic Instability and Leukemia in a Novel Mouse Model of Fanconi Anemia - Edwards, Donna M.; Mitchell, Dana K.; Abdul-Sater, Zahi; Chan, Ka-Kui; Sun, Zejin; Sheth, Aditya; He, Ying; Jiang, Li; Yuan, Jin; Sharma, Richa; Czader, Magdalena; Chin, Pei-Ju; et al. (Frontiers in Oncology, 2021)
Fanconi anemia (FA) is a disease of genomic instability and cancer. In addition to DNA damage repair, FA pathway proteins are now known to be critical for maintaining faithful chromosome segregation during mitosis. While impaired DNA damage repair has been studied extensively in FA-associated carcinogenesis in vivo, the oncogenic contribution of mitotic abnormalities secondary to FA pathway deficiency remains incompletely understood. To examine the role of mitotic dysregulation in FA pathway deficient malignancies, we genetically exacerbated the baseline mitotic defect in Fancc-/- mice by introducing heterozygosity of the key spindle assembly checkpoint regulator Mad2. Fancc-/-;Mad2+/- mice were viable, but died from acute myeloid leukemia (AML), thus recapitulating the high risk of myeloid malignancies in FA patients better than Fancc-/-mice. We utilized hematopoietic stem cell transplantation to propagate Fancc-/-; Mad2+/- AML in irradiated healthy mice to model FANCC-deficient AMLs arising in the non-FA population. Compared to cells from Fancc-/- mice, those from Fancc-/-;Mad2+/- mice demonstrated an increase in mitotic errors but equivalent DNA cross-linker hypersensitivity, indicating that the cancer phenotype of Fancc-/-;Mad2+/- mice results from error-prone cell division and not exacerbation of the DNA damage repair defect. We found that FANCC enhances targeting of endogenous MAD2 to prometaphase kinetochores, suggesting a mechanism for how FANCC-dependent regulation of the spindle assembly checkpoint prevents chromosome mis-segregation. Whole-exome sequencing revealed similarities between human FA-associated myelodysplastic syndrome (MDS)/AML and the AML that developed in Fancc-/-; Mad2+/- mice. Together, these data illuminate the role of mitotic dysregulation in FA-pathway deficient malignancies in vivo, show how FANCC adjusts the spindle assembly checkpoint rheostat by regulating MAD2 kinetochore targeting in cell cycle-dependent manner, and establish two new mouse models for preclinical studies of AML.